Potential impact of climate change on dietary grain protein content and its bioavailability-a mini review - Kashyap, Sindhu; Reddy, Bellam H. Rajashekar; Devi, Sarita; Kurpad, Anura V. (Frontiers in Nutrition, 2024)
The changing global climate brings a gradual yet constant and adverse shift in crop production. Grain crop plants, particularly cereals and legumes, respond varyingly to adverse climate, including reduction in grain yield and changes to their nutrient densities. An understanding of specific changes to crop systems under differing climatic conditions can help in planning diets to meet human nutrient sufficiency. Grain protein content is also affected by adverse environmental factors. Deficits in protein yield, linked to changes in grain or seed protein and antinutrient concentrations, have been reported in major food crops when exposed to elevated carbon dioxide, high temperature, drought, and humidity. These changes, in addition to affecting the quantity of indispensable or essential amino acids (IAA), also impact their bioavailability. Therefore, it is important to assess consequences of climate change on grain protein quality. An important tool to measure grain protein quality, is measuring its digestibility at the level of the ileum and its IAA concentration, linked to a metric called the Digestible IAA Score (DIAAS). A minimally invasive technique called the dual isotope tracer technique, which measures IAA digestibility after simultaneous administration of two different intrinsically labelled protein sources, one a test protein (2H/15N) and one a reference protein (13C) of predetermined digestibility, has been used in evaluation of grain protein IAA digestibility, and promises more in the evaluation of changes based on climate. This review discusses climate induced changes to grain protein quality through the prism of IAA digestibility, using the dual isotope tracer technique.